Local abnormal white matter microstructure in the spinothalamic tract in people with chronic neck and shoulder pain - Qiu, Zhiqiang; Liu, Tianci; Zeng, Chengxi; Yang, Maojiang; Xu, Xiaoxue (Frontiers in Neuroscience, 2025)
ObjectiveTo investigate differences in the microstructure of the spinothalamic tract (STT) white matter in people with chronic neck and shoulder pain (CNSP) using diffusion tensor imaging, and to assess its correlation with pain intensity and duration of the pain.Materials and methodsA 3.0T MRI scanner was used to perform diffusion tensor imaging scans on 31 people with CNSP and 24 healthy controls (HCs), employing the Automatic Fiber Segmentation and Quantification (AFQ) method to extract the STT and quantitatively analyze the fractional anisotropy (FA) and mean diffusivity (MD), reflecting the microstructural integrity of nerve fibers. Correlations of these differences with duration of pain and visual analog scale (VAS) scores were analyzed.ResultsNo significant differences in the mean FA or MD values of the bilateral STT were observed between people with CNSP and HCs (p > 0.05), as indicated by the two-sample t test. Further point-by-point comparison along 100 equidistant nodes within the STT pathway revealed significant reductions in FA values in the left (segments 12–18, 81–89) and right (segments 9–19, 76–80) STT in the CNSP group compared to HCs; significant increases in MD values were observed in the left (segments 1–13, 26–30, 71–91) and right (segments 8–17, 76–91) STT (p < 0.05, FWE corrected). Partial correlation analysis indicates that in people with CNSP, the FA values of the STT in regions with damaged white matter structure show a negative correlation with VAS scores and duration of pain, whereas MD values show a positive correlation with VAS scores and duration of pain.ConclusionThis study found that people with CNSP exhibit white matter microstructural abnormalities in the specific segments of STT. These abnormalities are associated with the patient’s pain intensity and disease duration. The findings offer a new neuroimaging perspective on the pathophysiological basis of chronic pain in the ascending conduction process and its potential role in developing targeted intervention strategies. However, due to the limited sample size and the lack of statistical significance when analyzing the entire spinothalamic tract, these conclusions should be interpreted with caution. Further research with larger cohorts is necessary to validate these results.